Design and development of alternative power generation system from heat sources - Jadin, Mohd Shawal; Mohamed, Amir Izzani; Ghazali, K. H. (2017)
Hybrid photovoltaic and thermoelectric systems more effectively convert solar energy into electrical energy. Two sources of energy are used in this project. One of the energy is solar energy that converts radiant light to electrical energy. The other one is heat energy, which converts heat energy into electrical energy. Therefore, this project will utilize both of the solar radiation and heat from the sun as to generate more electricity. The aim of this project is to build a hybrid system that will increase the efficiency of the power generation system. In this research, the output power of hybrid is equal to the sum of the maximum output power that produced separately from the individuals of PV module and TEG devices. The increasing of the maximum output power happens at 11.00 am until 12.00 at noon. The increasing is from 87.93 watts to 88.63 and from 91.98 watts to 99.27 watts respectively. While for the simulation, it was also shown the increasing in the output power. At the 11.00 am, it was starting to change from 72 watts to 74.3 watts and the other one is showing the same output power. In overall, with the using hybrid PV-TEG, the output that can be generated is higher than compared with an output power of the individual experiment.